Campus Canopy, 1943-01-15 - The Campus Canopy, The Georgia State Woman's College (Georgia State Womans College, 1943)
Upperclassmen Will Have Short Nutrition Course -- WAVE Ensign Visits GSWC Campus -- Date Bureau Plans Near Completion By Council Committee -- Ashley Named Head Of President Council -- Kimbrough, Beasley Added To Faculty -- Ruth Draper, Actress To Present Program Feb. 11 -- Bond Beauties Will Star At Soph Dance Next Week
Georgia State Womans College Student Newspaper
Keywords: Valdosta State University -- Periodicals